CONSTRUCTION AND ANALYSIS OF GPS ACCURACY FIELDS ON THE BASIS OF HARDWARE-SOFTWARE MEANS NI GPS SIMULATION TOOLKIT - O. N. Skrypnik; E. E. Nechaev; R. O. Arefev (Научный вестник МГТУ ГА, 2016)
Based on the application of hardware-software complex NI GPS Simulation Toolkit and aviation receiver CH-4312 proposed a method of constructing the fields of GPS precision according to the RAIM receiver (horizontal and vertical geometrical factor system) data. By comparing with experimental data the reliability of the obtained results is assessed and limitations on the conditions of use of the complex for investigation of the characteristics of the GPS were found. Built fields precision GPS for two areas of airspace, located in mid-and high latitudes were constructed.